FORMS OF CORRUPTION IN MEDIAEVAL SERBIA - Deretić, Nataša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Abstract: The consolidation of feudal relationships in the Serbian territories (of Raska and Duklja-Zeta) was slow and it remained within the range of ancestral / tribal relations and institutions for a long time, from the second half of 11th to 14th century. With the emergence of the mediaeval Serbian state and the development of a bureaucratic apparatus, accompanied by specialization in the spheres of judicial practice and finance, a new type of people appeared – judges and other persons dealing with justice, officials of the feudal lords. The more developed and ramified the bureaucratic apparatus (consisting of individuals), the more deviant conduct of people. They did not shrink from different forms of abuse (embezzlement, defamation, excessive charges, and various scams related to the ruler’s finances). The growing stratification in terms of social classes led to differentiation between those who were wealthy and the ones who were not. The former were increasingly recruited from the ranks of merchants and craftsmen, equally accustomed to deviant behaviour. What contributed to this was the fact that despite the principal allegiance to the Byzantine civilization, the Serbian state was not immune to western influences, coming mostly via coastal cities, but also from Hungary and other European states. The behaviour of mediaeval people was also influenced by the church, which in the territory of the mediaeval Serbia was a prominent economic, ideological and political force.